Investigating Factors Shaping Sunnah-Based Product Consumption among University Students - Anuar, Annurizal; Othman, Abdul Kadir; Maon, Siti Noorsuriani; Abdullah, Mohd Zulkifli; Dzulkipli, Mohd Redhuan; Mat Hasan, Noor Zaihan (Information Management and Business Review, 2024)
Health problems have increased because of modern lives, especially in young people because of poor nutrition and improper eating habits. Inspired by Islamic teachings, especially the Quran and the Sunnah of the Prophet Muhammad (PBUH), this study attempts to investigate the factors impacting Sunnah-based product consumption among Muslim college students. Data were gathered by utilizing a correlational research approach and questionnaires given to 476 Muslim university students. According to the study, 96.6% of respondents were aware of Sunnah-based products, and a sizable majority (93.9%) favored them. Childhood exposure to such products (44.3%) points to familial or cultural impacts. The frequency of consumption varied, though, with 41.8% consuming Sunnah-based goods on occasion. Taste concerns were negligible (12.0%) and accessibility issues (23.9%) emerged as the main obstacles to consumption, followed by high pricing (56.5%). Positive sentiments notwithstanding, real-world barriers impede widespread adoption. These results highlight how critical it is to remove obstacles preventing Muslim youth from using Sunnah-based products. Interventions can be designed to encourage healthy eating habits in line with Islamic teachings by knowing the factors influencing their decisions. This will ultimately improve the general health and well-being of Muslim communities.